Hierarchical assembly of an interlocked M8L16 container - Bloch, Witold M.; Holstein, Julian J.; Dittrich, Birger; Hiller, Wolf; Clever, Guido H. (Technische Universität Dortmund, 2018)
The self‐assembly of eight PdII cations and sixteen phenanthrene‐derived bridging ligands with 60° bite angles yielded a novel M8L16 metallosupramolecular architecture composed of two interlocked D4h‐symmetric barrel‐shaped containers. Mass spectrometry, NMR spectroscopy, and X‐ray analysis revealed this self‐assembled structure to be a very large “Hopf link” catenane featuring channel‐like cavities, which are occupied by NO3− anions. The importance of the anions as catenation templates became imminent when we observed the nitrate‐triggered structural rearrangement of a mixture of M3L6 and M4L8 assemblies formed in the presence of BF4− anions into the same interlocked molecule. Furthermore, the densely packed structure of the M8L16 catenane was exploited in the preparation of a hexyloxy‐functionalized analogue, which further self‐assembled into vesicle‐like aggregates in a reversible manner.
Keywords: Catenanes; Interlocked structures; Self-assembly; Structural transformations; Supramolecular chemistry; 540